TANGGUNG JAWAB ORGAN BUMN DALAM PENGELOLAAN KEKAYAAN BUMN DIKAITKAN DENGAN HAK NEGARA SEBAGAI PEMEGANG SAHAM - Tami Rusli (Law Faculty of Universitas Bandar Lampung, 2019)
ABSTRAK At present there is a dualism in the regulation of the management of BUMN Persero. First, arrangements that assume that state-owned enterprises are merely business entities. Secondly, the regulation which considers that the management of BUMN Persero is seen from the aspect of capital including into State Finance. This dualism of regulation brings different legal implications. This research is intended to find out and formulate, the responsibility of BUMN Persero in the management of BUMN Persero's wealth is associated with the rights of the State as a shareholder, the research method applied in this research is a normative juridical approach with analytical descriptive research which describes primary and secondary data related to the problem of responsibility legal management of BUMN Persero. The results of the research show that the responsibility of the management of BUMN Persero and BUMN BUMN organs is civil and the State has limited responsibility in accordance with the shares owned. Limited liability The Company's and the State's organs can be broken if they exceed the management authority according to the position of each organ (piercing the corporate veil). As a suggestion for the renewal of processes in the management of state-owned enterprises that are more supportive of quick, efficient and more accountable decision making, as well as the updating and structuring of the functions of institutions related to the management of state-owned enterprises.